Answer: -231 ft
<u>Step-by-step explanation:</u>
The submarine started at sea level = 0
It submerged 140 ft = -140 ft
It traveled 40 miles horizontally so it is still at -140 ft
It dove down an additional 120 ft = -260 ft <em>(-140 + -120)</em>
It traveled 25 miles horizontally so it is still at -260 ft
It rose 29 ft = -231 ft <em>(-260 + 29)</em>
Note: submerged and dove are negative values and rose is positive
0 - 140 - 120 + 29 = -231
Hello
So the question ask to simplify the said equation. In getting its answer base on that equation you must first factor out each of them then find out the common of them to cancel them out that could lead you to your answer. In my calculation, the answer is D. 8 open parentheses x plus 4 close parentheses over quantity x minus 6. I hope this would help you
Have a nice day
Answer:
D
Step-by-step explanation:
It is the organized one with the center bar also being the largest value.
<em>Complete Question:</em>
<em>Alicia is writing the program for a video game. For one part of the game she uses the rule (x,y)->(x-3,y+4) to move points on the screen. </em>
<em>A) what output does the rule give when the input is (-6,0)? </em>
<em>B)What output does the rule give when the input is (3,-4)? </em>
<em>C) Is the rule a function? Explain why it is or why it is not
</em>
Answer:
a. The output is (-9,4)
b. The output is (0,0)
c. See Explanation
Step-by-step explanation:
Given
Rule: (x,y)->(x - 3, y + 4)
Solving (a):
Inputs:
![x = -6](https://tex.z-dn.net/?f=x%20%3D%20-6)
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
The outputs is as follows;
![x => x - 3](https://tex.z-dn.net/?f=x%20%3D%3E%20x%20-%203)
![x => -6 - 3](https://tex.z-dn.net/?f=x%20%3D%3E%20-6%20-%203)
![x => -9](https://tex.z-dn.net/?f=x%20%3D%3E%20-9)
![y=> y + 4](https://tex.z-dn.net/?f=y%3D%3E%20y%20%2B%204)
![y=> 0 + 4](https://tex.z-dn.net/?f=y%3D%3E%200%20%2B%204)
![y=> 4](https://tex.z-dn.net/?f=y%3D%3E%204)
Hence:
The output is (-9,4)
Solving (b):
Inputs:
![x = 3](https://tex.z-dn.net/?f=x%20%3D%203)
![y = -4](https://tex.z-dn.net/?f=y%20%3D%20-4)
The outputs is as follows;
![x => x - 3](https://tex.z-dn.net/?f=x%20%3D%3E%20x%20-%203)
![x=>3-3](https://tex.z-dn.net/?f=x%3D%3E3-3)
![x = 0](https://tex.z-dn.net/?f=x%20%3D%200)
![y=> y + 4](https://tex.z-dn.net/?f=y%3D%3E%20y%20%2B%204)
![y=>-4+4](https://tex.z-dn.net/?f=y%3D%3E-4%2B4)
![y=>0](https://tex.z-dn.net/?f=y%3D%3E0)
Hence:
The output is (0,0)
Solving (c):
The function is a rule and the rule is that:
It shifts the graph left by 3 units and up by 4 units